2016
DOI: 10.3168/jds.2014-9289
|View full text |Cite
|
Sign up to set email alerts
|

Reticulo-rumen temperature as a predictor of calving time in primiparous and parous Holstein females

Abstract: The objective of this research was to define and analyze drops in reticulo-rumen temperature (Trr) as an indicator of calving time in Holstein females. Data were collected from 111 primiparous and 150 parous Holstein females between November 2012 and March 2013. Between -15 and -5 d relative to anticipated calving date, each female received an orally administered temperature sensing reticulo-rumen bolus that collected temperatures hourly. Daily mean Trr was calculated from d -5 to 0 relative to using all Trr v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Using CBT, Cagnacci et al, characterized the follicular phase by a 0.3 °C lower mesor, a 40% increase in the amplitude and a 90-minute advance in the daily nadir compared to the luteal phase [ 53 ]. Signal processing analysis of CCBT data has been demonstrated to be effective for detecting and predicting physiologic events of fertility, including ovulation, pregnancy, parturition, and spontaneous abortions [ 54 55 56 57 ].…”
Section: Continuous Assessment Of Cbt (Ccbt) and Utility Of Menstrualmentioning
confidence: 99%
“…Using CBT, Cagnacci et al, characterized the follicular phase by a 0.3 °C lower mesor, a 40% increase in the amplitude and a 90-minute advance in the daily nadir compared to the luteal phase [ 53 ]. Signal processing analysis of CCBT data has been demonstrated to be effective for detecting and predicting physiologic events of fertility, including ovulation, pregnancy, parturition, and spontaneous abortions [ 54 55 56 57 ].…”
Section: Continuous Assessment Of Cbt (Ccbt) and Utility Of Menstrualmentioning
confidence: 99%
“…The ability to detect drinking events using a thresholding method and by incorporating this information rather that removing it, as in previous studies (Cooper-Prado et al, 2011;Costa et al, 2016), has the potential to expand temperature monitoring in cows (Cooper-Prado et al, 2011;Timsit et al, 2011;Costa et al, 2016;Kovács et al, 2017). Drinking behavior in dairy cattle is important for the physical and emotional state of the animals (Baxter, 1983) and for farm economics because it is highly related to milk production (Steiger Burgos et al, 2001;Kramer et al, 2009;Daros et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that drinking events can be detected using a fixed threshold value of 37.7°C (Cooper-Prado et al, 2011;Costa et al, 2016). This was based on previous studies that used a small sample (n = 9 cows; Boehmer et al, 2009), or few water intake observations per cow (e.g., 3 data points per cow; Bewley et al, 2008b;Boehmer et al, 2009), or col- lected data under controlled experimental conditions (e.g., oral drench, water and feed restricted for up to 21 h; Bewley et al, 2008b;Boehmer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations